Experimental and numerical investigation of the scale‐up criterion of solid‐viscous fluid mixing in a stirred tank. (25th March 2021) - Lin, Daiqi; Wei, Hongyuan; Song, Erjia; Ng, Boonho; He, Ting; Dang, Leping
Abstract: The scale‐up of mixing processes is crucial for process engineering and power optimization in the chemical industry. Scale‐up of fluid mixing in stirred systems becomes a challenging task, especially when using non‐Newtonian fluids. In this study, computational fluid dynamics (CFD) has been applied to simulate the solid‐liquid mixing of silica particles with non‐Newtonian fluids of carboxymethyl cellulose (CMC) solutions (1.0, 1.5, and 2.0). The model is validated by experimental measurement of power consumption and solid‐phase concentration. The scale‐up criterion based on geometric similarity and constant tip speed is proved to be valid for non‐Newtonian systems by comparing kinematic similarity. The transformation of flow regime is discussed based on modified Reynolds number and local Reynolds number. The scale‐up criterion performs well in terms of the scale effect of power consumption, especially for the CMC2.0 solution system. This study is instructive for the scale‐up of non‐Newtonian fluid mixing in stirred tanks.